GNSS Jamming observed on Sounding Rocket Flights from Northern Scandinavia - Braun, Benjamin; Montenbruck, Oliver; Markgraf, Markus; Hörschgen-Eggers, Marcus; Kirchhartz, Rainer (European Navigation Conference 2024, 2024)
Since 2022, DLR’s Mobile Rocket Base (MORABA) has observed jamming of GNSS signals on sounding rockets launched from Esrange in northern Sweden and Andøya Space Center (ASC) in northern Norway. The jamming primarily affected the GPS L1, Galileo E1 and BeiDou B1C and B1I signals on the L1 frequency band and was noticeable through a pronounced reduction of the carrier-to-noise ratio of the received GNSS signals. Jamming was observed in northern Sweden at an altitude above 22 km and in northern Norway at an altitude above 36 km. Geometric consid-erations made it possible to roughly localize the source of the jamming signals from the points of the flight path marking the start and end of interference.